2020
DOI: 10.38038/vocatech.v2i1.40
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Self Efficacy Terhadap Kesiapan Kerja Mahasiswa Pendidikan Vokasi

Abstract: For humans, recognizing sounds is an easy thing, by listening carefully and understandingly to what is spoken and humans have intelligence in recognizing sound patterns. Unlike computers, the speech recognition process is a difficult process, this is because the computer requires a standard and logical mechanism to recognize sound patterns. With Mel Frequency Cepstral Coefficient (MFCC) method has an important role in determining the characteristics of a sound. This method is often used for verificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
2
7
0
5
Order By: Relevance
“…Menurut Wiharja et al (2020) kesiapan kerja sendiri yaitu keadaan proses lanjutan yang dialami oleh mahasiswa setelah mereka merasa siap dengan pengetahuan, keterampilan serta sikap yang diperlukan dalam dunia kerja. Kesiapan kerja menjadi faktor yang penting bagi mahasiswa setelah menyelesaikan pendidikan.…”
Section: Pendahuluanunclassified
“…Menurut Wiharja et al (2020) kesiapan kerja sendiri yaitu keadaan proses lanjutan yang dialami oleh mahasiswa setelah mereka merasa siap dengan pengetahuan, keterampilan serta sikap yang diperlukan dalam dunia kerja. Kesiapan kerja menjadi faktor yang penting bagi mahasiswa setelah menyelesaikan pendidikan.…”
Section: Pendahuluanunclassified
“…This is in line with relevant previous research. In his research, the researcher found that work readiness will be formed after a student goes through the educational process and gains experience (Wiharja MS et al, 2020). Moreover, the implementation of learning programs in SMK that prioritizes practice rather than theory has an important role, so that later SMK students are expected to have the ability, skills, and desire to be entrepreneurial (Utomo, 2017).…”
Section: Increasing Interest In Vocational Graduates In the Halal Tou...mentioning
confidence: 99%
“…Faktor internal lainnya yang berpengaruh terhadap kesiapan kerja siantaranya keterampilan atau softskill, sikap, bakat, serta motivasi. Kesiapan kerja yang dimiliki individu dapat dipengaruhi faktor internal yaitu, kecerdasan, keterampilan dan kecakapan, bakat, kemampuan dan minat, motivasi, kesehatan, kebutuhan psikologis, kepribadian, serta cita-cita dan tujuan dalam bekerja (Wiharja et al, 2020).…”
Section: Kerja (Meaning Of Work) Suatu Studi Etnografi Abdi Dalem Ker...unclassified